HYDROPHILIC POLYMER CHANGES THE WATER DEMAND IN THE IMPLEMENTATION OF A DWARF CASHEW ORCHARD - Gondim,Rubens S. (2020)
ABSTRACT Important losses of dwarf cashew seedlings during the establishment of orchards in the Brazilian semiarid are related to the relatively short rainy season. This study aimed to evaluate biochar and hydrophilic polymer as soil amendments to increase water retention and reduce plant death in the first year. An experiment was conducted at the Curu Station, Paraipaba, CE, Brazil, using the clone BRS 226. The experimental design consisted of randomized blocks, with amounts of 0.5, 1.0, 2.0, and 4.0 kg of cashew wood biochar and 20, 40, 60, 80 g of hydrophilic polymer applied per pit, as well as a control treatment (no soil amendment). Seedlings were submitted to an irrigation regime to avoid water stress (5 L water seedling−1 when the tensiometer installed at a depth of 0.15 m reached 60 kPa). The variables of plant development number of leaves, plant height, stem diameter, and canopy diameter were evaluated up to 374 days after transplanting to the field. The analysis of variance showed no treatment effect on plant development. However, minimum water consumption was observed when 29.56 g of hydrophilic polymer was applied per pit, providing 100.0% seedling survival.